Hierarchical Disordered Colloidal Thin Films with Duplex Optical Elements for Advanced Anti‐Counterfeiting Coding. Issue 24 (28th October 2020) - Bai, Ling; Lim, Yun; He, Yuheng; Xiong, Qirong; Hou, Shuai; Zhang, Jun; Duan, Hongwei
Abstract: Multiscale structures are found in nature to impart brilliant structural colors with integrated properties of multiple optical elements. However, it remains challenging to build more than one optical element into artificial photonic materials in practical manufacturing. Here, hierarchical disordered photonic superstructures (HDPSs) with optical properties arising from tailored interplay of thin‐film interference (TFI) and coherent scattering from amorphous colloidal arrays (ACAs) are fabricated through the combined use of infiltration‐driven colloidal assembly and micro‐imprinting. Uniform thin ACA films with TFI effects (ACA‐TFIs) are first coated on premium glossy photo papers, displaying near‐isotropic colors under natural light and mixed colors upon specular lighting due to the duplex optical effects. Such collective effects are easily modulated by the film thicknesses of ACA‐TFIs. Also, micro‐imprinting that can remove a patterned monolayer of particles from ACA‐TFI films causes suppressed TFI in the imprinted regions, leading to HDPS films with encoded optical features. Collectively, HDPS anti‐counterfeiting labels with covert and sophisticated optical coding are achieved and their enhanced complexity results in infinite possible optical features that are virtually impractical to forge, opening new avenues to high‐level security applications. Abstract : Hierarchical disordered photonic superstructures, with collective optical properties arising from the interplay of thin‐film interference and coherent scattering from arrays of colloidal particles, are fabricated through the combined use of infiltration‐driven colloidal assembly and micro‐imprinting technique. These approaches allow to flexibly manipulate the collective optical features and to design sophisticated optical coding for high‐level anti‐counterfeiting applications.